Menopausal hormone therapy and new-onset diabetes in the French Etude Epidemiologique de Femmes de la Mutuelle Générale de l'Education Nationale (E3N) cohort - De Lauzon-Guillain, Blandine (Springer Verlag, 2009)
AIMS/HYPOTHESIS: Two US randomized trials found a lower incidence of type 2 diabetes among women treated by menopausal hormone therapy (MHT) with oral conjugated equine estrogen combined with medroxyprogesterone acetate. The purpose of this study was to evaluate the influence of various MHTs, according to their formulation and route of administration, on new-onset diabetes in a cohort of postmenopausal French women. METHODS: The association between MHT use and new-onset diabetes was investigated by Cox regression analysis in 63,624 postmenopausal women of the French E3N cohort. Cases of diabetes were identified through self-report or drug reimbursement record linkage, and further validated. RESULTS: 1220 new-onset diabetes cases were validated. We observed a lower risk of new-onset diabetes among women having ever used MHT (Hazard ratio: HR=0.82 [0.72 – 0.93]), compared to MHT never users. Adjustment for BMI during follow-up rather than baseline BMI did not substantially modify this association. An oral route of estrogen administration was associated with a greater decrease in diabetes risk than a cutaneous route (HR=0.68 [0.55–0.85] vs 0.87 [0.75–1.00], P for homogeneity=0.028). When further taking into account the type of progestagen used in combined MHT, we were not able to show significant differences between progestagens. CONCLUSION: MHT appeared to be associated with a lower risk of new-onset diabetes. This relation was not mediated by changes in BMI. Further studies are needed to confirm the stronger effect of oral administration of estrogen compared to cutaneous administration.